Optimizing plasmonic characteristics of Ag-AuNPs/Nanohillocks Si Heterostructures for efficient SERS performance - Alwan, M. Alwan (Universiti Malaysia Perlis (UniMAP), 2020)
Link to publisher's homepage at http://ijneam.unimap.edu.my